In situ PCR for detection and identification of fungal species - Bindslev, L.; Oliver, Richard; Johansen, B. (2002)
PCR and DNA sequence analysis have become standard tools for identification, detection and phylogenetic analysis of fungi. A large number of species are incapable of growth in the laboratory, making the preparation of pure DNA problematical. The amplification of DNA samples from impure material is subject to misinterpretation if more than one species is present. To overcome this problem, we designed an in situ PCR technique that links PCR amplification to the light microscopic image. The amplified tissue is stained, thus confirming which morphotype has been amplified. The PCR product can then be sequenced. We tested the technique on fixed Blumeria graminis spores and mycelia using primers derived from the sequence of the gene encoding the catalytic subunit of protein kinase A (bkal). This is the first report of in situ PCR on phytopathogenic fungal material. This technique allows positive confirmation of the origin of genes cloned from obligate pathogenic fungi and could be adapted for use on any samples containing mixed fungal species.